2023
DOI: 10.1111/risa.14122
|View full text |Cite
|
Sign up to set email alerts
|

Are the good spared? Corporate social responsibility as insurance against cyber security incidents

Abstract: Despite the increasing consensus that socially responsible behavior can act as insurance against externally induced shocks, supporting evidence remains somewhat inconsistent. Our study provides a clear demonstration of the insurance‐like properties of corporate social responsibility (CSR) in preserving corporate financial performance (CFP), in the event of a data (cyber) breach. Exploring a sample of 230 breached firms, we find that data breaches lead to significantly negative CFP outcomes for low CSR firms, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
1
0
2
Order By: Relevance
“…(2023) also observed that the link between CSR performance and firm value is stronger during crises, augmenting the value of CSR as a ‘strategic risk‐mitigating tool’ (Bamiatzi et al. , 2023, p. 1). Relatedly, some studies find a positive association between CSR responses to COVID‐19 and firm performance (Huang and Liu, 2021; Yi, Zhang and Yan, 2021); yet others find no effect (Bae et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(2023) also observed that the link between CSR performance and firm value is stronger during crises, augmenting the value of CSR as a ‘strategic risk‐mitigating tool’ (Bamiatzi et al. , 2023, p. 1). Relatedly, some studies find a positive association between CSR responses to COVID‐19 and firm performance (Huang and Liu, 2021; Yi, Zhang and Yan, 2021); yet others find no effect (Bae et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Серія «Економіка і менеджмент», випуск 1 (93), 2023 яння кращому маркетингу продуктів і послуг (Lee et al, 2022), створюючи непередбачені можливості і сприяючи набуттю соціальної легітимності (Carson, 2020). Крім того, КСВ може функціонувати подібно до реклами, збільшуючи попит на продукти і послуг та/або зниження чутливості споживчих цін (Tuan et al, 2019) і навіть може надавати компаніям можливості розвивати нематеріальні активи, такі як гудвіл (Alshurafat et al, 2023), а також може виступати у ролі страхування від інцидентів у сфері кібербезпеки (Bamiatzi et al, 2023).…”
Section: вісник сумського національного аграрного університетуunclassified
“…У наукових працях, що живляться неокласичною економічною теорією, стверджується, що КСВ підвищує витрати фірми, ставлячи фірму в невигідне конкурентне становище порівняно з конкурентами (Jensen, 2002). Грунтуючись на агентській теорії, деякі дослідження також стверджують, що витрачання цінних ресурсів фірми на ведення КСВ призводить лише до значних управлінських переваг, а не до фінансових вигод для акціонерів фірми (Brammer & Millington, 2008). Навпаки, інші вчені стверджують, що здійснення діяльності з КСВ може мати позитивний вплив на продуктивність фірми шляхом забезпечення кращого доступу до цінних ресурсів (Cai & Le, 2023), залучення та утримання висококваліфікованих співробітників (Basu & Basu, 2011), спри-…”
unclassified